Досвід організації роботи поліції Ізраїлю та можливості його застосування в Україні - Гусаров, С. М.; Gusarov, S. M.; Сергій Гусаров (Вісник Харківського національного університету внутрішніх справ. - 2015. - № 3 (70). - С. 11-21., 2015)
Досліджено організацію, завдання та функції поліції Ізраїлю. Особливу увагу приділено особливостям діяльності добровільних помічників поліції Ізраїлю, їх завданням та основним напрямам роботи. На підставі проведеного аналізу запропоновано впровадження позитивного досвіду роботи добровільних помічників поліції Ізраїлю в діяльність Національної поліції України.

The organization, tasks and functions of Israel police have been studied. The procedure of selecting candidates on police positions and some elements of police service have been researched. Special attention is paid to the peculiarities of the activity of volunteers of Israel police, in particular, the author has considered the tasks and functions of the division, which is in charge of their activities’ organization; the author has also considered directions of using volunteers of the police, requirements to the candidates to volunteers, some elements of service by such volunteers. Based on the conducted analysis the author has suggested implementing a positive experience of the activities of volunteers of Israel police into the activity of the National Police of Ukraine.

Исследовано организацию, задачи и функции полиции Израиля. Особое внимание уделено особенностям деятельности добровольных помощников полиции Израиля, их задачам и основным направлениям работы. На основании проведенного анализа предложено внедрение положительного опыта работы добровольных помощников полиции Израиля в деятельность Национальной полиции Украины.
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; Україна. Ukraine. Украина; Наукові публікації. Scientific publications. Научные публикации; Ізраїль; поліція; добровільний помічник; громадськість; Israel; police; volunteer; public; Израиль; полиция; добровольный помощник; общественность